Relationship between physical concern and anxiety sensitivity in females with panic disorder: The moderating role of distress tolerance - Babayie, Kimia; Abdolhoseini, Amir; Saydi, Zahra; Mousavi, SeyedMillad (International Journal of Applied Behavioral Sciences, 2023)
Background & Aim: Panic disorder showed higher prevalence in female than male. The aim of the present study was to investigate the moderating role of distress tolerance in the relationship between physical concern and anxiety sensitivity of females with panic disorder symptoms in female students. Materials & Methods: The present study conducted through a descriptive cross-sectional method. The statistical population of this research included all the female students of Islamic Azad University of Ilam branch in 2022(N=2009). Of all students 323 cases were selected using the available sampling method. The data collected through standard questionnaire i.e. severity of panic disorder (SMPD-A) (2013), distress tolerance of Simons and Gehr (2005), anxiety sensitivity of Floyd et al. (2005) and physical concern of Littleton et al. (2005). The statistical method used for data analysis was Baron and Kenny and bootstrap. Results: The results confirmed model of relationship between physical concerns and anxiety sensitivity with panic disorder symptoms with the moderating role of distress tolerance. The correlation coefficient between physical concerns with panic disorder symptoms was 0.468, anxiety sensitivity with panic disorder symptoms was 0.425, and distress tolerance with panic disorder symptoms was -0.462. Conclusion: It is believed that several factors cause vulnerability to panic disorder. Many stressful situations of daily life and the inability to adapt to frequent life stress can disrupt cognitive function in people, which can trigger many psychiatric disorders in susceptible people and aggravate the severity of symptoms in people